The Application of Blockchain Technology in Financial Technology Systems as a Preventive Effort to Prevent Personal Data Leakage - Vaganti Safa Sukma Rubianti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In today's digital era, conveniences abound. We can conduct all activities online, from studying and playing, shopping, and paying taxes such as property tax (PBB), education fees, and electricity. We no longer need to carry large amounts of cash in our wallets because payments can be made online using financial technology. This study aims to determine the potential for implementing blockchain technology as a preventative measure against personal data leaks in financial technology systems. This study uses a normative juridical research method with a legal and conceptual approach to test the legal certainty of blockchain technology's application in financial technology systems. The results show that blockchain offers a secure and hack-resistant security system due to its decentralized and immutable nature. Therefore, no one can manipulate or destroy transaction data recorded in blocks. However, this immutable and decentralized nature presents challenges in fulfilling the rights of personal data subjects. Collaborative efforts are needed between the government and financial technology service providers to strengthen blockchain technology regulations and infrastructure to create legal certainty and a robust security system that can mitigate the risk of personal data leaks.